2021
DOI: 10.12659/ajcr.931570
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Year-Old Boy and a 14-Year-Old Girl Initially Diagnosed with Toxic Shock Syndrome and Tested Positive for SARS-CoV-2 Infection, Supporting a Diagnosis of Multisystem Inflammatory Syndrome in Children (MIS-C)

Abstract: Case series Patients: Male, 7-year-old • Female, 14-year-old Final Diagnosis: Multisystem inflammatory syndrome in children (MIS-C) Symptoms: Muscular weakness • shock Medication: — Clinical Procedure: — Specialty: Critical Care Medicine • Infectious Diseases • Pediatrics and Neonatology • Rheumatology Objective: Unusual clinical course Background: Multisystem inflammatory syndrome in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Several articles report cases of virally induced myositis or myopathy (89)(90)(91)(92)(93)(94)(95)(107)(108)(109). Some describe various (98).…”
Section: Viral Myositismentioning
confidence: 99%
“…Several articles report cases of virally induced myositis or myopathy (89)(90)(91)(92)(93)(94)(95)(107)(108)(109). Some describe various (98).…”
Section: Viral Myositismentioning
confidence: 99%
“…Myositis is a rare complication of SARS-CoV-2. A review of the literature has identified 31 case studies describing a total of 40 cases of COVID-19-associated myositis [7,12,14,15,30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Case reports were selected for review if they described virally-induced cases with associated idiopathic inflammatory myopathy or myositis correlating with recent exposure to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…No cases of patients with prior autoimmune history were included. Patients with history of myositis concurrent with or developed postinfection comprised 31 (78%) of these cases [7,12,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], while myositis developed in the setting of vaccination comprised nine (22%) of the cases [14,15,30,[36][37][38][39]. In regard to MSA/MAA testing, 18 of the cases did not mention testing, two cases reported other specialized testing without MSAs/MAAs, and one case reported "negative immunologic tests" without definitive results.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, rhabdomyolysis was the presenting symptom [26,29]. Both myositis and rhabdomyolysis may occur as a part of MIS-C [22,30]. There have been several reports of acute benign childhood myositis in the pandemic period, attributed to influenza or COVID-19 [31].…”
Section: Neuromuscular Manifestations Of Covid-19 In Childrenmentioning
confidence: 99%